Effect of wilting on silage quality of tropical grasses harvested at different intervals - Singh, A P; Samanta, A K; Misra, A K; Upadhyay, V S (The Indian Journal of Animal Sciences, 2012)
An experiment was conducted to investigate the effect of different cuts and wilting on silage quality of Pennisetum trispecific hybrid (TSH: a cross of P. americanum x P. purpureum x P. squamulatum) and guinea grass (Gu: Panicum maximum). Harvesting of grasses was done at 30-35 days interval after the onset of monsoon and defined as first, second. and third cuts. Chopped grasses were wilted in shade for 24 hr. After 60 days of ensiling. silos were opened for analysis. Based on physical parameters, silage quality was better in all cuts of wilted forages. Relatively higher level of lactic acid was found in first (2.77%) and second (2.73%) cuts of wilted TSH silage and was lowest in second cut of unwilted guinea grass silage (0.1 %). Butyric acid was nil in all the cuts of wilted TSH silages and a minute amount present in wilted guinea grass silages(O.07 - 0.18%). The results indicated that wilting substantially improved the quality of silage.